Commentary on the Constitution of India - Basu, D. D. ("Gurgaon, Haryana", 2008)
Commentary on the Constitution of India. Being a comparative treatise on the universal principles of justice and constitutional government with special reference to the organic instrument of India.
Keywords: Indian Constitution